Soft/elastic nanopatterned biointerfaces in the service of cell biology - Platzman, Ilia; Gadomska, Katarzyna Maria; Janiesch, Jan-Willi; Louban, Ilia; Cavalcanti-Adam, Elisabetta A.; Spatz, Joachim P. (Micropatterning in cell biology ; A, 2014)
Engineering of biomimetic interfaces has become a valuable tool for guiding cellular processes such as adhesion, spreading, motility, as well as proliferation, differentiation, and apoptosis. The interaction of cells with the extracellular matrix (ECM) or with other cells is involved in nearly every cellular response in vivo. Recent wide-ranging evidence shows that crosstalk between different environmental stimuli can have a tremendous impact on various cell functions. Therefore, the defined control of these stimuli in vitro can contribute to the understanding of the mechanisms underlying the ability of cells to perform “intelligent” missions like acquiring, processing, and responding to environmental information. This chapter summarizes recently developed nanopatterned biomimetic systems that allow independent control of different stimuli and illustrates their applications in cellular studies. Particular attention is devoted to nanopatterned 2D and 3D artificial ECM systems based on poly(ethylene glycol) materials. These allow independent control over the material elasticity and the nanoscale distribution of bioligands on the surface. In the case of engineering artificial cellular interfaces, additional attention has to be devoted to the critical functions of protein transport regulators, namely the cell membrane and the dynamic actin cytoskeleton; both are essential for the signaling activity of individual proteins and the entire cell.